Heterologous vaccination (ChAdOx1 and BNT162b2) induces a better immune response against the omicron variant than homologous vaccination - Jaeeun Yoo; Younjeong Kim; Yu mi Cha; Jaewoong Lee; Yeon Jeong Jeong; Si-Hyun Kim; Lisa L. Maragakis; Seungok Lee (Journal of Infection and Public Health, 2023)
Background: The ongoing COVID-19 pandemic has seen the emergence of numerous novel variants of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. In this study, we compared the efficacy of three different forms of immunization against the wild-type, delta, and omicron variants of the virus: two doses of the BNT or AZ vaccine (BNT/BNT or AZ/AZ) as homologous vaccination, three doses of AZ/AZ/BNT as heterologous vaccination, and naturally occurring immunization in severe COVID-19 cases. Methods: We collected serum samples from vaccine recipients (67 receiving BNT/BNT, 111 receiving AZ/AZ, and 18 receiving AZ/AZ/BNT) and 46 patients who were admitted to the hospital with severe COVID-19. Blood samples were taken one month after the last injection and the efficacy of the vaccination was determined using the surrogate virus neutralization test (sVNT), with a positive result defined as an inhibition rate of over 30%. Serum samples from COVID-19 patients were taken at various points during their hospitalization and tested for inhibition rates. Results: Our results indicated that there was no notable difference in the levels of neutralizing antibodies (nAb) in vaccine recipients and patients against the wild-type and delta variants. However, when it came to the omicron variant, the vaccine recipients had significantly lower nAb titers. Among the vaccine recipients, those who received a booster dose of BNT after their first two doses of AZ (AZ/AZ/BNT) demonstrated the highest level of protection against the omicron variant at 44.4%, followed closely by the COVID-19 patients. In analyzing the serial samples taken from hospitalized COVID-19 patients, we observed that their inhibition rates against the wild-type and delta variants improved over time, while the inhibition rate against the omicron variant decreased. Conclusion: In conclusion, our findings suggest that heterologous booster vaccination after primary vaccination produces higher nAb titers and provides a higher level of protection against the omicron variant compared to primary vaccination alone. This protective effect was similar to that observed in patients with severe COVID-19.